Deciphering sedimentary organic matter sources: Insights from radiocarbon measurements and NMR spectroscopy. (11th February 2015) - Sanderman, Jonathan; Krull, Evelyn; Kuhn, Thomas; Hancock, Gary; McGowan, Janine; Maddern, Todd; Fallon, Stewart; Steven, Andy
Abstract In a sediment core collected from an estuary in a rapidly urbanizing region in South East Queensland, Australia, we used multiple geochemical tracers to understand the provenance, form, and rate of accumulating organic matter (OM) focusing on the application of two tools often used in studies of soil OM: solid‐state 13C nuclear magnetic resonance (NMR) spectroscopy and interpretation of radiocarbon (14C) data by modeling the uptake of the bomb‐spike in atmospheric 14C. While elemental (C, N) and stable isotope (13C, 15N) data generally could not distinguish OM sources, these data did indicate that there has been a steady increase in nutrient loading to the estuary and that there were periodic deposition events where the OM was dominated by C3 terrestrial vegetation. The NMR results showed that the OM was primarily of terrestrial origin being dominated by lignin and stable char‐like carbon compounds in all samples. The 14C data and modeling indicated that the OM was composed of a mixture of material with widely varying ages. In general, the OM was hundreds of years older than the age of the sediments as determined by fallout radionuclide dating (1950–2009 chronology), indicating that a large fraction of the OM has resided on the terrestrial landscape for a substantial period before being transported and buried in the estuary sediments. By applying this combination of techniques, we have been able to develop a coherent picture of a very complex deposition and accumulation history in these estuary sediments.